Interventions to prevent disability in frail community-dwelling elderly: a systematic review - van Rossum Erik; Daniels Ramon; de Witte Luc; Kempen Gertrudis IJM; van den Heuvel Wim (BMC Health Services Research, 2008)
Abstract Background There is an interest for intervention studies aiming at the prevention of disability in community-dwelling physically frail older persons, though an overview on their content, methodological quality and effectiveness is lacking. Methods A search for clinical trials involved databases PubMed, CINAHL and Cochrane Central Register of Controlled Trials and manually hand searching. Trials that included community-dwelling frail older persons based on physical frailty indicators and used disability measures for outcome evaluation were included. The selection of papers and data-extraction was performed by two independent reviewers. Out of 4602 titles, 10 papers remained that met the inclusion criteria. Of these, 9 were of sufficient methodological quality and concerned 2 nutritional interventions and 8 physical exercise interventions. Results No evidence was found for the effect of nutritional interventions on disability measures. The physical exercise interventions involved 2 single-component programs focusing on lower extremity strength and 6 multi-component programs addressing a variety of physical parameters. Out of 8 physical exercise interventions, three reported positive outcomes for disability. There was no evidence for the effect of single lower extremity strength training on disability. Differences between the multi-component interventions in e.g. individualization, duration, intensity and setting hamper the interpretation of the elements that consistently produced successful outcomes. Conclusion There is an indication that relatively long-lasting and high-intensive multicomponent exercise programs have a positive effect on ADL and IADL disability for community-living moderate physically frail older persons. Future research into disability prevention in physical frail older persons could be directed to more individualized and comprehensive programs.